Górny Śląsk oczami chińskiego studenta. Familoki. Śląskie mikrokosmosy i Słownik śląsko-chiński jako materiały uzupełniające w glottodydaktyce polonistycznej .......... 153 - Przybylska, Renata; Rak, Maciej; Ruszer, Andrzej; Li, Yinan (70 lat polonistyki Pekińskiego Uniwersytetu Języków Obcych: Dziedzictwo, rozwój, innowacje, 2025)
UPPER SILESIA THROUGH THE EYES OF A CHINESE STUDENT. FAMILIOKI. ŚLĄSKIE MIKROKOSMOSY AND SŁOWNIK ŚLĄSKO-CHIŃSKI AS SUPPLEMENTARY MATERIALS IN POLISH GLOTTODIDACTICSKatowice is an academic center that attracts students not only from Poland but also from around the world each year. Among them are students from China who are learning Polish as a foreign language at the University of Silesia. The university is a significant point on the map of Upper Silesia, a region that, due to its complex history, has preserved a distinct language, culture, attachment to traditions, cuisine, work ethos, and industrial character, all of which shape the regional identity of its inhabitants. One of the books addressing this topic is Familoki. Śląskie mikrokosmosy by Kamil Iwanicki. Published in 2023, this work is a valuable source of knowledge for foreigners learning Polish, who, as part of their studies, are not only learning the language but also the culture, particularly that which is specific to this region of Poland. As a supplement, it is also worthwhile to utilize Słownik śląsko-chiński by Marek Jachymski. Therefore, the article presents the glottodidactic potential of these two publications in working with students from China, for whom reading them may be the first step in discovering the rich culture of Upper Silesia.